2012
DOI: 10.1007/s00418-012-0956-x
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor modulates claudins and tight junctional functions in ovarian cancer cell lines

Abstract: Ovarian adenocarcinomas, like human ovarian surface epithelial cells, form functional tight junctions. Tight junction molecules claudin-3 and claudin-4, which are the receptors of Clostridium perfringens enterotoxin (CPE), are abnormally upregulated in epithelial ovarian cancers of all subtypes including, mucinous cystadenocarcinoma and serous cystadenocarcinoma. Clostridium perfringens enterotoxin may be a novel tumor-targeted therapy for ovarian cancers. In epithelial ovarian cancers, overexpression of epide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…This receptor is mainly present in the basolateral region and can thus potentially induce neoplastic transformation, as suggested previously [14], [19], [38]. Controversially to our observations, a recent study showed that EGF decreased claudin-3 and -4 via MEK/ERK and/or PI3K/Akt signaling pathways in ovarian cancer cell lines [39]. The reasons for the discrepancy observed are currently unclear but may be related to tissue-specific differences in claudin function or even the tissue microenvironment features, as previously discussed [40].…”
Section: Discussionsupporting
confidence: 81%
“…This receptor is mainly present in the basolateral region and can thus potentially induce neoplastic transformation, as suggested previously [14], [19], [38]. Controversially to our observations, a recent study showed that EGF decreased claudin-3 and -4 via MEK/ERK and/or PI3K/Akt signaling pathways in ovarian cancer cell lines [39]. The reasons for the discrepancy observed are currently unclear but may be related to tissue-specific differences in claudin function or even the tissue microenvironment features, as previously discussed [40].…”
Section: Discussionsupporting
confidence: 81%
“…However, EGF mediated the alternation of claudin protein expression are a great difference and depend on the different cell type and tumor as previous described. For instance, a recent study showed that EGF induced downregulation of CLDN3 in mucinous cystadenocarcinoma via the MEK/ERK or PI3K/Akt signaling pathway by inducing degradation of the TJ proteins with changes in structures and functions [25]. Conversely, upregulation of CLDN3 play fundamental role to promote the development of colorectal cancer, which is potentially regulated by the EGF-activated downstream pathway, ERK1/2 and PI3K-Akt signaling pathways [30].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, EGF was mediated the upregulation of CLDN 1, 3 and 4, and downregulation of CLDN 2, which increased the force of intercellular barrier in MDCK-II cells [23, 24]. In addition, EGF may also regulate the expression functions of claudins in ovarian and colon cancer cells during cancer development via the EGF-activated ERK1/2 and PI3K-Akt pathways [25, 26]. However, its regulatory mechanism in ADC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Recently this mechanism of the TJ protein regulation in ovarian cancers was explored by treating both ovarian mucinous and serous cystadenocarcinoma cell lines with EGF [71]. EGF was found to downregulate claudin-3 in mucinous ovarian carcinoma cell lines and claudin-4 in ovarian serous cystadenocarcinoma by inducing the degradation of these proteins with also changes in the structure and function of TJ via the MEK/ERK or PI3K/AKT signaling pathway.…”
Section: Structure and Function Of Claudinsmentioning
confidence: 99%